Pengaruh Alternative Dispute Resolution Terhadap Pergeseran Tren Penyelesaian Sengketa Melalui Jalur Litigasi - Ahmad Zaid Al Baihaqi; Dera Marshanda; Asep Suherman (GLOBAL SCIENTS PUBLISHER, 2025)
Business disputes often arise from differing interpretations of the parties' rights and obligations. Although Law No. 30 of 1999 regulates Alternative Dispute Resolution (ADR) as an alternative to out-of-court dispute resolution, business actors in Indonesia still tend to choose litigation due to its binding legal force and the certainty of enforceable decisions. This study aims to examine the factors inhibiting the implementation of ADR and describe the concept of